2007
DOI: 10.1002/app.27484
|View full text |Cite
|
Sign up to set email alerts
|

In vitro release of salicylic acid through poly(vinyl alcohol‐g‐itaconic acid) membranes

Abstract: In this study, itaconic acid (IA) was grafted on poly(vinyl alcohol) (PVA) at two different grafting percentages, 7.0% (w/w) and 14.0% (w/w), and membranes were prepared from the grafted copolymer (PVA-g-IA). Performances of PVA and PVA-g-IA membranes for the transdermal release of salicylic acid (SA) at in vitro conditions were investigated by using 2.0 mg/mL SA solutions. Effect of the pH on the release of SA was studied by keeping pH of donor and acceptor solutions in a range of (2.1-7.4). Permeation studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…A characteristic band at 3320–3300 cm −1 was observed corresponding to the OH stretching vibration of the PVA hydroxyl groups. Signals were also observed at 1735 cm −1 and 1300–1000 cm −1 corresponding to both the CO stretching vibration and the CO stretching vibration of the ester linkage, respectively . As expected, the intensity of both signals increased with TA content, due to an increase in esterification.…”
Section: Resultssupporting
confidence: 70%
“…A characteristic band at 3320–3300 cm −1 was observed corresponding to the OH stretching vibration of the PVA hydroxyl groups. Signals were also observed at 1735 cm −1 and 1300–1000 cm −1 corresponding to both the CO stretching vibration and the CO stretching vibration of the ester linkage, respectively . As expected, the intensity of both signals increased with TA content, due to an increase in esterification.…”
Section: Resultssupporting
confidence: 70%
“…Asman and Şanlı25 studied the ultrafiltration of Fe(III) solutions in the presence of poly(vinyl alcohol) with modified poly(methyl methacrylate‐ co ‐methacrylic acid) membranes. They concluded that retention was low because of the mostly un‐ionized poly(methacrylic acid) units of the membrane at low pH values.…”
Section: Resultsmentioning
confidence: 99%
“…The separation process will be successful if the polymer reagent employed meet the following requirements [5]: high affinity towards the target metal ion, inactivity towards the non-target metal ion, high molecular mass, possibility of regeneration, chemical and mechanical stability, low toxicity, and low cost. Considering these requirements, basic, neutral, and acid hydrophilic polymers have been designed and investigated respect to the analytical determination of metal ions [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. These WSPs can be synthesized by different routes such as radical, cationic, and spontaneous polymerization, but the most usual synthetic procedures are addition polymerization, especially radical polymerization, and by functionalizing polymer backbone through polymer-analogous reactions.…”
mentioning
confidence: 99%